Revisiting Grammatical versus Pragmatic Competence in Learning a Language - Retnowaty Retnowaty (Kompetensi : Jurnal Pendidikan dan Humaniora Fakultas Keguruan dan Ilmu Pendidikan UNIBA, 2022)
This study aims to revisit the difference between grammatical and pragmatic competence in language learning. This paper design is library research by studying books, journals, literature, notes, and reports related to grammatical and pragmatic competence. The data sources for this project report are relevant books and previous studies in the form of journal articles about grammatical and pragmatic competence. Result of the study stated that knowing only grammatical or language rules without knowing when and where the rules must be applied is insufficient. It addresses not only grammar but also meaning. This could imply that there should be more practice exercises for identifying grammatical and pragmatic errors. The teachers should then encourage their students to be aware of grammatical and pragmatic errors and treat them seriously. As a result, this study has brought this issue to light and may aid language learners in developing their pragmatic ability.